Pengaruh Kualitas Produk, Harga, dan Lokasi terhadap Kepuasan Konsumen UMKM Abon Farda Kediri - Dhea Pinky Cafrina Alif; Indah Listyani; Adi Trisna Wahyudi (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyze the influence of product quality (X1), price (X2), and location (X3) on consumer satisfaction (Y) at UMKM Abon Farda Kediri. The research uses a quantitative approach with both primary and secondary data. The sample consists of 64 respondents, and the data were collected through questionnaires, literature reviews, and documentation. The analytical methods applied include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t-test, F-test, and the Coefficient of Determination test. The results of the analysis show the multiple linear regression equation: Y = 5.464 + 0.297X1 + 0.280X2 + 0.165X3 + e. Based on the t-test, the product quality variable has a t-value of 2.132 with a significance level of 0.037, indicating a significant effect on consumer satisfaction. The price variable has a t-value of 2.284 with a significance level of 0.026, also showing a significant influence. However, the location variable records a t-value of 1.176 with a significance level of 0.244, meaning it does not significantly affect consumer satisfaction. The F-test results show an F-value of 8.223 with a significance level of 0.000, confirming that product quality, price, and location simultaneously have a significant effect on consumer satisfaction. Therefore, product quality and price play an important role in increasing consumer satisfaction at UMKM Abon Farda Kediri.